Using communicative approach in Arabic language classroom to develop Arabic speaking ability - Che Haron, Sueraya (International Institute for Science, Technology & Education (IISTE), 2014)
Studies have shown that most Malay learners of Arabic language exhibit weak performance in speaking Arabic despite spending years of learning the language. Among the causes of the problem are traditional methods like reading, translation, and memorization that are popularly used in the teaching and learning of Arabic language. Since Arabic language is not widely used in Malaysian society, the only chance the students have to speak Arabic is in the classroom. Therefore the researcher designed a series of classroom activities using communicative approach for a period of 14 weeks on 45 students of Islamic Education minoring in the Teaching of Arabic as Second Language at the Institute of Education at the International Islamic University Malaysia. Surveys were administered to the students before and after the communicative activities took place. In addition the researcher also performed classroom observation and collected self reports from the students after each activity. The results from paired sample t-test showed that students’ perception on Arabic speaking and ability to speak Arabic improved after 14 weeks. In addition level of difficulty faced to speak Arabic decreased gradually. Results from the Pearson Product Moment correlation coefficient suggested that the improved perceptions of speaking Arabic lessened the difficulties faced by students in speaking Arabic. The results also suggested that the improved perceptions towards speaking Arabic increased students’ ability to speak Arabic.